2005
DOI: 10.1530/rep.1.00457
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of action of angiotensin II on mammalian sperm function

Abstract: Angiotensin II (AII) stimulates capacitation and fertilizing ability in mammalian spermatozoa, with the binding of AII to its receptors resulting in stimulation of cAMP production in both uncapacitated and capacitated cells. This study investigated possible mechanisms whereby AII affects cAMP availability. The first question was whether extracellular Ca 21 is required for responses in mouse spermatozoa and, using chlortetracycline fluorescence analysis, it was clear that cells responded to AII only when the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 27 publications
3
5
0
1
Order By: Relevance
“…Consistent with other studies we have carried out (e.g. Mededovic and Fraser, 2005), pertussis toxin on its own had no detectable effect (Figure 9). However, when used in combination with genistein and daidzein, it was able to block the usual stimulatory responses obtained with these xenobiotics.…”
Section: Series Vii: Pertussis Toxin Blocks Responses To Xenobioticssupporting
confidence: 93%
See 2 more Smart Citations
“…Consistent with other studies we have carried out (e.g. Mededovic and Fraser, 2005), pertussis toxin on its own had no detectable effect (Figure 9). However, when used in combination with genistein and daidzein, it was able to block the usual stimulatory responses obtained with these xenobiotics.…”
Section: Series Vii: Pertussis Toxin Blocks Responses To Xenobioticssupporting
confidence: 93%
“…Uncapacitated mouse sperm suspensions were incubated for approximately 35 min in the presence of 10 nmol/l genistein with/without 100 μmol/l ddAdo (n = 3). Used on its own, ddAdo had no significant effect, again consistent with other studies using ddAdo in a similar system (Baxendale and Fraser, 2003a;Mededovic and Fraser, 2005). When used with genistein, however, ddAdo essentially blocked the responses to the xenobiotic ( Figure 10).…”
Section: Series Viii: Dideoxyadenosine Blocks Responses To Xenobioticssupporting
confidence: 87%
See 1 more Smart Citation
“…Further investigation confirmed that pertussis toxin does indeed have different effects on responses to FPP and to AII, suggesting that the initial step in response to these two first messengers is different for the two peptides. Since both stimulate cAMP production in uncapacitated suspensions, it seems likely that binding of AII to its receptor stimulates cAMP in an indirect manner, possibly by altering intracellular Ca 2+ concentration (18). Immunolocalization studies revealed that AII receptors ,like the receptors for FPP, adenosine and calcitonin, are located on both the acrosomal cap and along the flagellum of mouse and human spermatozoa (17).…”
Section: Other First Messengers In Seminal Plasma and Their Specific mentioning
confidence: 99%
“…Os peptídeos são degradados por um limitado número de enzimas com uma especificidade de substrato relativamente ampla (ROQUES et al, 1993) (VINSON et al, 1995;KÖHN et al, 1998). A AngII aumenta a motilidade, hiperativa e capacita o espermatozóide (VINSON et al 1996), porém não inibe a perda espontânea do acrossoma, tanto em espermatozóides humanos quanto de ratos (MEDEDOVIC & FRASER, 2005). A AngII eleva a concentração de AMPc em espermatozóides capacitados e incapacitados (MEDEDOVIC & FRASER, 2004).…”
Section: Peptídeos E Peptidasesunclassified